Impact of aerosols on liver xenobiotic metabolism: A comparison of two methods of exposure. (March 2022) - Bovard, David; Renggli, Kasper; Marescotti, Diego; Sandoz, Antonin; Majeed, Shoaib; Pinard, Lucile; Ferreira, Sandra; Pak, Claudius; Barbier, Anaïs; Beguin, Alexandre; Iskandar, Anita; Frentzel, Stefan; et al.
Abstract: Assessment of aerosols effects on liver CYP function generally involves aqueous fractions (AF). Although easy and efficient, this method has not been optimized recently or comparatively assessed against other aerosol exposure methods. Here, we comparatively evaluated the effects of the AFs of cigarette smoke (CS) and Tobacco Heating System (THS) aerosols on CYP activity in liver spheroids. We then used these data to develop a physiological aerosol exposure system combining a multi-organs-on-a-chip, 3D lung tissues, liver spheroids, and a direct aerosol exposure system. Liver spheroids incubated with CS AF showed a dose-dependent increase in CYP1A1/1B1, CYP1A2, and CYP2B6 activity and a dose-dependent decrease in CYP2C9, CYP2D6, and CYP3A4 activity relative to untreated tissues. In our physiological exposure system, repeated CS exposure of the bronchial tissues also caused CYP1A1/1B1 and CYP1A2 induction in the bronchial tissues and liver spheroids; but the spheroids showed an increase in CYP3A4 activity and no effect on CYP2C9 or CYP2D6 activity relative to air-exposed tissues, which resembles the results reported in smokers. THS aerosol did not affect CYP activity in bronchial or liver tissues, even at 4 times higher concentrations than CS. In conclusion, our system allows us to physiologically test the effects of CS or other aerosols on lung and liver tissues cultured in the same chip circuit, thus delivering more in vivo like data. Highlights: Comparison of medium bubbled with aerosol vs. physiological aerosol exposure system on liver CYP activity. Physiological system = 3D lung and liver tissues, a microfluidic and a direct aerosol exposure system. Bubbled medium induces CYP1A1/1B1, CYP1A2, and CYP2B6 and inhibits CYP2C9, CYP2D6 and CYP3A4. Using the physiological system, CS induces CYP1A1/1B1, CYP1A2 and CYP3A4. Data from the physiological exposure system are closer to data obtained in smokers.